Construction of a mobile game for learning Libras - Guess teaching - João A. F. Furquim; Flávia B. Blum Haddad; Débora G. Ribeiro Dias (Journal on Interactive Systems)
The social inclusion of people with disabilities depends on everyone. To collaborate with the inclusion of deaf people, this article addresses the construction of a game available on mobile platforms to assist in learning Brazilian Sign Language (Libras). The game proposes challenges and rewards through questions and answers and also presents Libras signs created by an avatar. As a background, it comments on the importance and emergence of educational games and highlights the history of Libras, presenting concepts, definitions, and curiosities of this little-explored language. The methods and tools for building the game are detailed so that they can be replicated in other related projects. The results present the game’s prototypes up to the final version, in addition to the performance and results of usability tests to improve the game and performance tests to evaluate the user’s learning curve.